Replication Data for “Learning Together: Experimental Evidence on the Impact of Group-Based Nutrition Interventions in Rural Bihar" - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
This dataset contains baseline (2016) and endline (2018) data from a two-round panel dataset that focuses on 2246 rural women from 24 gram panchayats (GPs) in three blocks of the eastern Indian state of Bihar. The sampling of these women was based on two eligibility criteria: (1) they or someone in their household must be a member of a Self-Help Group (SHG), and (2) they must have a child aged 6 months to 2 years at the time of the baseline survey conducted in 2016. The 24 GPs were divided into treatment and control arms equally. Women in the treatment arm received the JEEViKA-MC interventions, while those in the control arm did not receive any specific interventions. The dataset includes information on various primary and secondary outcomes, individual, household, and village characteristics, as well as many other key variables related to the impact pathways being studied.